The views of general practitioners in Morocco about health promotion at the primary health care services: Qualitative study - Ouassim Mansoury; Hamza Kachkhouch; Samira Essoli; Adil Mansouri; Murtada Jabbar; Latifa Adarmouch; Mohamed Amine; Majda Sebbani (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Health promotion (HP) is one of the key skills that every general practitioner (GP) should have, according to The World Organization of Family Doctors, but for several reasons, his practice remains insufficient. However, a gap would exist between the GPs' knowledge and their practices about HP. The aims of our study were to explore GPs' perceptions, knowledge, and practices in Morocco about HP and identify their barriers and needs to best practice HP actions. MATERIALS AND METHODS: A qualitative case study was conducted among GPs, via semi-structured interviews following an interview guide. Purposive and snowball sampling were used to select our sample. It contained four themes, perceptions, practices, barriers and needs, and proposals for improvement. The interviews were recorded and then transcribed. Thematic content data analysis was done manually. Favorable ethical approval was obtained from the local ethics committee. RESULTS: Fourteen GPs participated in this study. The sex ratio was at one. GPs' practices were focused on the biomedical model with wide confusion of HP with prevention and therapeutic education. Their roles in HP were considered paramount. The number of patients during consultations, structures' care, and knowledge were the main barriers. The main cited needs were material resources and HP training. CONCLUSION: Our study has made it possible to make an inventory of the practice of HP in Morocco. Participants' practices were based on the curative aspect. There is a crucial need to implement continuing and contextualized training for general practitioners to strengthen their skills in HP. This training will help to succeed in the health-promoting hospital's strategy.